SILENCE AND EXILE IN A MAÇÃ NO ESCURO, BY CLARICE LISPECTOR (Muitas Vozes, 2021)
The aim of this text is to study Clarice Lispector's novel A maçã no escuro (1970), addressing themes such as testimony and exile, thinking on these characterizations considering the crime committed by the main character, Martim – he attempted to murder his wife – and his consequent escape (thus, for being a fugitive, Martim tries to hide his past, although he does not feel guilty for his act). In this way, we intend to analyze his almost amoral condition and his refusal to speak/testify about his experience; as well as to think about his new world (on his way to scape, he finds shelter in a farm) not as reappropriation, but as refusal and power of denying. From this experience, we think it is possible to delimit a space of exile, which is shown through silence and loss of language. To do so, this text will be mainly supported by authors such as Giorgio Agamben (2008), Jean-Luc Nancy (1996) and Maurice Blanchot (2003).